Meta Analisis terhadap Peran Kepala Sekolah sebagai Pemimpin Perubahan - Putriana Kusuma Wardani; Teguh Triwiyanto (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the leadership role of the principal in changes in the school organization. This research uses a qualitative approach with a meta-analysis method which is carried out by analyzing data obtained from several previously existing studies. The results of the data analysis show that the principal as a leader of change in the school organization has a very important role, namely: (1) building and growing awareness of all elements of the school regarding the urgency of change; (2) create and develop a vision, mission, goals, strategies, and policies for school change by including the participation of all elements of the school; (3) communicate the vision, mission, objectives, strategies, and policies to obtain improvements and feedback; (4) provide support, motivation, and empowerment of school resources for a smooth process of change; (5) planning and striving for the realization of short-term benefits of change; (6) consolidate all elements of the school to realize the success of school change; (7) demonstrate commitment and do what is said; (8) evaluate to determine the success rate of changes and improvements that need to be made; and (9) hold celebrations by giving awards (rewards) to all elements of the school.